Second‐line immunotherapy and functional outcomes in autoimmune encephalitis: A systematic review and individual patient data meta‐analysis. Issue 9 (26th June 2022) - Halliday, Amy; Duncan, Andrew; Cheung, Mike; Boston, Ray C.; Apiwattanakul, Metha; Camacho, Ximena; Bowden, Stephen; D'Souza, Wendyl
Abstract: Autoimmune encephalitis (AE) is a neurological disorder caused by autoimmune attack on cerebral proteins. Experts currently recommend staged immunotherapeutic management, with first‐line immunotherapy followed by second‐line immunotherapy if response to first‐line therapy is inadequate. Meta‐analysis of the evidence base may provide higher quality evidence to support this recommendation. We undertook a systematic review of observational cohort studies reporting AE patients treated with either second‐line immunotherapy or first‐line immunotherapy alone, and outcomes reported using the modified Rankin Scale (mRS; search date: April 22, 2020). We performed several one‐stage multilevel individual patient data (IPD) meta‐analyses to examine the association between second‐line immunotherapy and final mRS scores (PROSPERO ID CRD42020181805). IPD were obtained for 356 patients from 25 studies. Most studies were rated as moderate to high risk of bias. Seventy‐one patients (71/356, 19%) were treated with second‐line immunotherapy. We did not find a statistically significant association between treatment with second‐line immunotherapy and final mRS score for the cohort overall (odds ratio [OR] = 1.74, 95% confidence interval [CI] = .98–3.08, p  = .057), or subgroups with anti‐N‐methyl‐D‐aspartate receptor encephalitis (OR = 1.03, 95% CI = .45–2.38, p  = .944) or severe AE (maximum mRS score > 2; OR = 1.673, 95% CI = .93–3.00, p  = .085). Treatment with second‐line immunotherapy was associated with higher final mRS scores in subgroups with anti‐leucine‐rich glioma‐inactivated 1 AE (OR = 6.70, 95% CI = 1.28–35.1, p  = .024) and long‐term (at least 12 months) follow‐up (OR = 3.94, 95% CI = 1.67–9.27, p  = .002). We did not observe an association between treatment with second‐line immunotherapy and lower final mRS scores in patients with AE. This result should be interpreted with caution, given the risk of bias, limited adjustment for disease severity, and insensitivity of the mRS in estimating psychiatric and cognitive disability.